2008
DOI: 10.1107/s1600536807068067
|View full text |Cite
|
Sign up to set email alerts
|

Triammonium hexahydroxidooctadecaoxidohexamolybdogallate(III) heptahydrate

Abstract: The title compound, (NH4)3[GaMo6(OH)6O18]·7H2O, contains two centrosymmetric GaMo6 B-type Anderson cluster units consisting of central GaO6 octa­hedra surrounded by a hexa­gonal assembly of MoO6 edge-sharing octa­hedra. Like other B-type Anderson clusters, where the central Mo atom is substituted with a di- or trivalent metal ion, the central six μ3-oxido bridges are protonated. The average Ga—O bond length is 1.97 (1) Å, whereas the average Mo—O distances are 2.29 (2), 1.94 (1) and 1.709 (5) Å, respectively, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The cluster assumes a near D 3d symmetry with dimensions ~8.6 × 8.6 × 2.7 Å and has been isolated with fifteen different heteroatoms till now [X: Al (Lee et al, 1991; Manikumari et al, 2002; Shivaiah et al, 2002; Martin et al, 2004; Shivaiah and Das, 2005; Liu et al, 2006; Dhara et al, 2007; Cao et al, 2008; Zhou et al, 2009), Cr (Perloff, 1970; An et al, 2006; Yu et al, 2006; Lee, 2007; Zhou and Yang, 2007; Shi D. et al, 2008; Shi D. M. et al, 2008; Zhang et al, 2008, 2014; Singh et al, 2010b, 2014; Li et al, 2011; Singh and Ramanan, 2011; Kumar et al, 2014a; Joo et al, 2015), Mn (He et al, 2012; Oms et al, 2012; Rosnes et al, 2012, 2013; Yan et al, 2012; Zhang et al, 2012, 2015a,b; Hutin et al, 2013; Ai et al, 2014; Yvon et al, 2014), Fe (Wu et al, 2001), Co (Nolan et al, 1996; Panneerselvam et al, 1996; Lee and Joo, 2000a; Lee et al, 2001; Martin et al, 2004), Ni (Lee et al, 2002; Liu et al, 2007; Liu F.-X. et al, 2008), Cu (Ito et al, 1989), Zn (Allen et al, 1997), Ga (Mensinger et al, 2008; Himeno et al, 2009), Te (Evans, 1948; Kondo et al, 1980; Robl and Frost, 1993a,b; Lorenzo-Luis et al, 1999; Drewes et al, 2004a,b; Charushnikova et al, 2005; Drewes and Krebs, 2005; Gao et al, 2007; Liu Y. et al, 2008; Yan et al, 2008), Rh (Ozawa et al, 1991), Pd (Ozawa et al, 1991), Sb (Ogawa et al, 1988; Yan et al, 2014), I (Kondo et al, 1980; Rosu and Weakley, 2000; An et al, 2005)and Pt (Lee and Sasaki, 1984; Lee, 1994; Lee and Joo, 2000b, …”
Section: Introductionmentioning
confidence: 99%
“…The cluster assumes a near D 3d symmetry with dimensions ~8.6 × 8.6 × 2.7 Å and has been isolated with fifteen different heteroatoms till now [X: Al (Lee et al, 1991; Manikumari et al, 2002; Shivaiah et al, 2002; Martin et al, 2004; Shivaiah and Das, 2005; Liu et al, 2006; Dhara et al, 2007; Cao et al, 2008; Zhou et al, 2009), Cr (Perloff, 1970; An et al, 2006; Yu et al, 2006; Lee, 2007; Zhou and Yang, 2007; Shi D. et al, 2008; Shi D. M. et al, 2008; Zhang et al, 2008, 2014; Singh et al, 2010b, 2014; Li et al, 2011; Singh and Ramanan, 2011; Kumar et al, 2014a; Joo et al, 2015), Mn (He et al, 2012; Oms et al, 2012; Rosnes et al, 2012, 2013; Yan et al, 2012; Zhang et al, 2012, 2015a,b; Hutin et al, 2013; Ai et al, 2014; Yvon et al, 2014), Fe (Wu et al, 2001), Co (Nolan et al, 1996; Panneerselvam et al, 1996; Lee and Joo, 2000a; Lee et al, 2001; Martin et al, 2004), Ni (Lee et al, 2002; Liu et al, 2007; Liu F.-X. et al, 2008), Cu (Ito et al, 1989), Zn (Allen et al, 1997), Ga (Mensinger et al, 2008; Himeno et al, 2009), Te (Evans, 1948; Kondo et al, 1980; Robl and Frost, 1993a,b; Lorenzo-Luis et al, 1999; Drewes et al, 2004a,b; Charushnikova et al, 2005; Drewes and Krebs, 2005; Gao et al, 2007; Liu Y. et al, 2008; Yan et al, 2008), Rh (Ozawa et al, 1991), Pd (Ozawa et al, 1991), Sb (Ogawa et al, 1988; Yan et al, 2014), I (Kondo et al, 1980; Rosu and Weakley, 2000; An et al, 2005)and Pt (Lee and Sasaki, 1984; Lee, 1994; Lee and Joo, 2000b, …”
Section: Introductionmentioning
confidence: 99%
“…The metal-exchange phenomenon has been exhibited in several examples of polyoxometalate structures. Electrospray ionization mass spectroscopy (ESI-MS) characterization was used to identify mixed-metal phosphate-centered Keggin ions in aqueous tungsten and phosphododecametalate solutions. , Similar experiments for niobate/tantalate and Mo/V–selenite systems showed additional mixed-metal species. Altering the pH conditions of monomeric salt solutions has led to the substitution of the central metal ion of Keggin Al 13 by Ga, Fe, or Ge as well as a variety of di- and trivalent metal ions into the Anderson cluster [Mo 7 O 24 ] 6– . We explored the potential for metal exchange in tridecameric clusters and discovered that such a process occurs when mixing Al 13 and In­(NO 3 ) 3 . As a result indium ions substitute into the exterior metal sites of the cluster to produce Al 7 In 6 (Figure ).…”
Section: Introductionmentioning
confidence: 99%
“…2-8 On the other hand, a number of Anderson-type Mo VI complexes, [M(OH) 6 Mo 6 O 18 ] 3/4have already been prepared from aqueous solution. [18][19][20][21][22][23][24][25][26][27] In fact, the present study found the formation of [Ga(OH) 6 Mo 6 O 18 ] 3in aqueous Mo VI -Ga III system (pH 1.3-5). Thus, a cis-MoO 2 arrangement is usually found for the polyoxomolybdate structure.…”
Section: Discussionmentioning
confidence: 49%
“…11- 17 The group II, III elements are known to form Anderson-type Mo VI complexes with planar configuration in aqueous solution. [18][19][20][21][22][23][24][25][26][27] Although Gao et al recently prepared Keggin-type [XMo 12 O 40 ] 6-(X = Co II , Ni II ) complexes, 28 the preparation of Keggin-type Mo VI complexes with the group II, III elements seems still challenging in the POM chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation